2018
DOI: 10.53841/bpscpf.2018.1.307.15
|View full text |Cite
|
Sign up to set email alerts
|

Are clinical psychologists, psychotherapists and counsellors overlooking the needs of their male clients?

Abstract: Around 75 per cent of suicides are male, yet men seek therapy less than women do. Is talking about feelings unappealing to men? Our interviews with 20 experienced therapists identified ways in which therapy might be made more male-friendly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“… Liddon et al (2018) and Kung et al (2003) suggested that men do not seek counseling for emotional disturbances, which is a common presenting issue for women. Men are more likely to present to counseling with a solution-focused agenda, whereas women are more inclined toward emotional exploration ( Holloway et al, 2018 ; Liddon et al, 2018 ; Tamres et al, 2002 ). The conventional focus of counseling must be modified to meet men’s specific mental health needs.…”
mentioning
confidence: 99%
“… Liddon et al (2018) and Kung et al (2003) suggested that men do not seek counseling for emotional disturbances, which is a common presenting issue for women. Men are more likely to present to counseling with a solution-focused agenda, whereas women are more inclined toward emotional exploration ( Holloway et al, 2018 ; Liddon et al, 2018 ; Tamres et al, 2002 ). The conventional focus of counseling must be modified to meet men’s specific mental health needs.…”
mentioning
confidence: 99%